The Impact of Online Destination Brand Experience, Destination Brand Authenticity and Tourist Destination Image on Behavioral Intentions - Aflit Nuryulia Praswati; Nanda Martiya Wardani; Muhammad Rohim (Journal of Indonesian Tourism and Development Studies, 2021)
This paper aims to investigate online destination brand experience, destination brand authenticity, and tourist destination image on behavioral intentions of Solo Raya tourist destinations. In this study, a sample of areas was taken, namely several tourist areas of Solo Raya, which included Surakarta, Karanganyar, Sragen, Boyolali, Sukoharjo, and Klaten, who actively use social media in seeking information about several tourist destinations in Solo Raya. The sample in this investigation was 414 respondents. Types and sources of data in this investigation are quantitative data, which is primary data obtained through questionnaires. The sampling technique was using a purposive sampling technique. The data collection method used in this research is by allocating an opinion poll online using Google Forms. The results suggest that objective online destination brand experience, destination brand authenticity, and tourist destination image positively affect behavioral intentions toward the destination.Keywords: Behavioral intentions toward the destination, destination brand authenticity, online destination brand experience, tourist destination image.